Transcriptome analysis provides insight into adaptive mechanisms of scallops under environmental stress - Mao, Junxia; Huang, Xiaofang; Sun, Hongyan; Jin, Xin; Guan, Wenjuan; Xie, Jiahui; Wang, Yiying; Wang, Xubo; Yin, Donghong; Hao, Zhenlin; Tian, Ying; Song, Jian; et al. (Frontiers in Marine Science, 2022)
High temperature and hypoxia greatly threaten marine life and aquaculture. Scallops, a diverse and ecologically important group of high economic value, mostly thrive in fluctuating environments, and are vulnerable to environmental stress. In the present study, the molecular response mechanism of scallops to a combination of environmental stressors was investigated via transcriptome analysis of the gill tissues in three scallop species, the Yesso scallop (Patinopecten yessoensis), Zhikong scallop (Chlamys farreri) and bay scallop (Argopecten irradians) that were exposed to transient heat, hypoxia and a combination thereof. The Yesso scallop had the most differentially expressed genes (DEGs) compared with the other two scallop species, indicating the highest sensitivity of the Yesso scallop to environmental stress. With increased temperature and decreased dissolved oxygen, the number of DEGs was greatly increased in the three scallop species, indicative of the enhancement in gene expression regulation in scallops in response to severe environmental changes. Heat and hypoxia had a synergistic effect on scallops. GO and KEGG enrichment analysis of DEGs under different stressors revealed overlapping molecular mechanisms of response in scallops following exposure to heat and hypoxia. Several immune and apoptosis-related pathways were highly enriched in the upregulated DEGs of the three scallops, suggesting that immune system activation and apoptosis promotion occurred in scallops in response to environmental stress. Heat shock proteins (HSPs) were significantly upregulated under heat and hypoxia, which likely assisted in correct protein folding to facilitate the adaption of the scallops to the altered environment. Additionally, the HIF-1 signaling pathway—the key pathway associated with hypoxia response—was triggered by extremely acute environmental changes. Comparative transcriptome analysis revealed 239 positively selected genes among the different scallops, including those involved in immune system and environmental adaptation, suggesting a long-term mechanism of environmental adaptation. The present study provides new insights into the molecular response mechanism in scallops to multiple environmental stressors and improves our understanding of the adaptive mechanisms of marine organisms under changing global climate conditions.